Geographic and socioeconomic variation of sodium and potassium intake in Italy: results from the MINISAL-GIRCSI programme. Issue 9 (10th September 2015) - Cappuccio, Francesco P; Ji, Chen; Donfrancesco, Chiara; Palmieri, Luigi; Ippolito, Renato; Vanuzzo, Diego; Giampaoli, Simona; Strazzullo, Pasquale
Abstract : Objectives: To assess geographic and socioeconomic gradients in sodium and potassium intake in Italy. Setting: Cross-sectional survey in Italy. Participants: 3857 men and women, aged 39–79 years, randomly sampled in 20 regions (as part of a National cardiovascular survey of 8714 men and women). Primary outcome measures: Participants' dietary sodium and potassium intakes were measured by 24 h urinary sodium and potassium excretions. 2 indicators measured socioeconomic status: education and occupation. Bayesian geoadditive models were used to assess spatial and socioeconomic patterns of sodium and potassium intakes accounting for sociodemographic, anthropometric and behavioural confounders. Results: There was a significant north-south pattern of sodium excretion in Italy. Participants living in southern Italy (eg, Calabria, Basilicata and Puglia >180 mmol/24 h) had a significantly higher sodium excretion than elsewhere (eg, Val d'Aosta and Trentino-Alto Adige <140 mmol/24 h; p<0.001). There was a linear association between occupation and sodium excretion (p<0.001). When compared with occupation I (top managerial), occupations III and IV had a 6.5% higher sodium excretion (coefficients: 0.054 (90% credible levels 0.014, 0.093) and 0.064 (0.024, 0.104), respectively). A similar relationship was found between educational attainment and sodium excretion (p<0.0001). When compared with those with a university degree, participants with primary and junior school education had a 5.9% higher urinary sodium (coefficients: 0.074 (0.031, 0.116) and 0.038 (0.001, 0.075), respectively). The socioeconomic gradient explained the spatial variation. Potassium excretion was higher in central regions and in some southern regions. Those in occupation V (low-skill workers) showed a 3% lower potassium excretion compared with those in occupation I. However, the socioeconomic gradient only partially explained the spatial variation. Conclusions: Salt intake in Italy is significantly higher in less advantaged social groups. This gradient is independent of confounders and explains the geographical variation.